PRODUK KAD KREDIT ISLAM DAN APLIKASINYA DI BANK ISLAM MALAYSIA BERHAD (BIMB) - Mansor, Fadillah (Jurnal Syariah, 2019)
This article discusses with details on Islamic credit card, the operation and the application of Shariah principles in Islamic credit card instruments offered by Bank Islam Malaysia Berhad (BIMB).